Water use of wheat, corn and sunflower in the semiarid pampas = Uso del agua por trigo, maíz y girasol en la región semiárida pampeana - Bono, Angel Alfredo (2017)
Crop water use in semiarid environments allows designing management strategies to improve water use efficiency. Our objective was to estimate wheat (Triticum aestivum L.), maize (Zea mays L.) and sunflower (Helianthus annuus L.) water use in the Semiarid Pampas of Argentina and to identify the relative contribution from soil and from in-season rainfall. Data were collected from 138 field experiments conducted during 2000-2013 over an area of 15 Mha. Soil water content was measured 3-4 times during the crop growing season, in a total of 552 soil profile moisture determinations. Soil samples were taken every 20 cm in the entire rooting zone. Gravimetric water content was converted to stored water using measured bulk density. Rainfall during crop growing cycle was measured at each experimental site. Crop water use was calculated as the difference between soil water content at sowing minus the soil water content at harvest plus rainfall received during the growing season. Runoff and drainage were estimated and discounted from crop water use. Water use efficiency was estimated as the ratio between grain yield and crop water use. Water losses as runoff and drainage rounded 15% among the three crops. Average water use was 319 mm for wheat, 487 mm for maize, and 443 mm for sunflower while respective water use efficiencies were 7.3, 18.6 and 5.6 kg DM grain ha-1 mm-1 respectively. Approximately 90% of water used by crops corresponded apparently to the in-season rainfall whereas the contribution from stored soil water at sowing was relatively low, except in dry years when it represented around 25% of in-season crop water use.